Pirates of the Caribbean the curse of the black pearl - Bruckheimer, Jerry; Verbinski, Gone; Walt Disney Pictures ([New York] : Walt Disney, 2003)
The roguish yet charming Captain JAck Sparrow's (Johny Deep) idyllic pirate life capsizes after his nemesis, the wily Captain BArbossa (Geoffrey Rush) steals his ship, Black Pearl), and later attacks the town Port Royal, kidnapping the governor's beautiful daughter Elizabeth (Keira Knightley)
Title from title screen
Bonus features: An epic at sea, fly on the set, diaries, below deck, blooper reel, deleted scenes, moonlight serenade scene progression, image gallery, pirates in the parks
Executive producers, Mike Stenson...[et al.] ; edited by Craig Wood, Stephen Rivkin, A.C.E. Arthur Schmidt ; director of photography, Dariusz Wolski
Cast: Johny Deep, Geoffrey Rush, Orlando Bloom, Keira Knightley Jonathan Pryce
DVD Format
In English or Thai woth optional English, Thai, Korean, Bahasa or Mandarin subtitles
Keywords: Pirates -- Drama; Suspense in motion pictures